Death by a thousand cuts: The health implications of black respectability politics - Lee, Hedwig (Souls, 2016)
The authors introduce the concept of “vigilance,” capturing behaviors that reflect attempts to navigate racialized social spaces on a daily basis. Specifically, vigilant behaviors include care about appearance and language to be treated with respect, avoidance of social spaces, and psychological preparation for potential prejudice and discrimination. Furthermore, these behaviors align with those discussed in Black respectability politics debates. Using data from a population-representative sample of Black adults in Chicago, they report that vigilance is associated with poor physical and mental health indexed through chronic health conditions, depressive symptoms, and self-rated health.